Elementos da Governança Pública para gestão dos Conselhos Sociais: um estudo no Conselho Estadual dos Direitos da Pessoa Idosa (CEDPI/MS) - JOSIANE SILVA PEREIRA (2025)
This study investigates the elements of public governance in the management of social councils, focusing on the State Council for the Rights of the Elderly of Mato Grosso do Sul (CEDPI/MS). The research aims to analyze public governance applied to CEDPI/MS, identifying its structural and functional elements, as well as proposing improvements to strengthen its performance. The methodology employed includes a systematic literature review and a documentary analysis, covering meeting minutes, relevant legislation, and deliberations from state conferences. This qualitative research, with a descriptive and exploratory approach, seeks to understand how public governance is manifested in the council's functioning. The results indicate that CEDPI/MS faces challenges related to transparency, public participation, accountability, and efficiency in carrying out its functions. The analysis of minutes and documents reveals difficulties in the effective participation of civil society, resource management, and the implementation of public policies aimed at the elderly population. Based on the evidence obtained, the study proposes an action plan to enhance governance at CEDPI/MS, including the creation of monitoring mechanisms, the expansion of social participation, and greater integration with other public agencies. It is concluded that strengthening governance in social councils is essential to ensuring rights and promoting the inclusion of the elderly in the formulation and implementation of public policies.